Fungsi dan Kedudukan Kelembagaan Pemerintahan Desa menurut UU No 6 tahun 2014 - esti ningrum; wahyu hariadi (Faculty of Law, Universitas Wijayakusuma, 2022)
With the reform of the 1945 Constitution of the Republic of Indonesia, regarding the re-arrangement of villages, this can be read in Article 18B paragraph 2 which reads